Optimal vector control of three-phase induction motor - Tamimi, Jasem; Jaddu, Hussein (ACTA Press, 2006)
This paper presents the optimal solutions of the induction motor (IM) fluxes and currents that minimize the total energy of the motor. A second order model based on vector control approach relating motor fluxes (states) and currents (controls) is considered. Optimal state and control trajectories of IM are obtained by solving algebraic Riccati equation. In addition, the simulation results for different weight are presented. Also this paper considers and compares between two cases based on the second order model.
Keywords: Induction machine, vector control, optimal control.